Pengenalan Bahan Makanan Berkualitas Pada Ibu Hamil Kek Di Puskesmas Simpang Tiga Kota Pekanbaru Tahun 2020: Bahan Makanan Berkualitas - winda septiani; Kamali Zaman; Nurhapipa Nurhapipa (STIKes Hang Tuah Pekanbaru, 2021)
The transition period from childhood to adulthood often causes teenagers to experience problems. This period occurs between the ages of 10 to 19 years and is not married. The Indonesian Society of Dermatology and Venereology (INSDV) report the number of sexually transmitted diseases (STDs) for adolescents in Indonesia was increased from 2017. The exposure of adolescents to STDs can be triggered by juvenile delinquency such as premarital sexual relations, drugs, free sex which has an impact on pregnancy out of marriage, dropping out of school, early marriage, abortion, risk of childbirth, STDs. Efforts to anticipate juvenile delinquency are through the establishment of the Youth Integrated Service Post (YISP). It is part of the CAE program (Children, Adolescents and Elderly), as the flagship program of the Ministry of Health, and implemented at the Surabaya City Health Office. This program puts forward a preventive approach because it focuses on primary health care activities holistically. This program is the collaboration with the Benowo Public Health Center (PHC), Surabaya City Government, which aims to foster YISP through health education to solve problems during puberty. This activity was attended by 24Â youth assisted by the Benowo PHC. Health education activities were provided through a combination lecture method with the visual education method (documentary video screening), and at the end of the activity, the evaluation of adolescent knowledge was carried out. The results of community service activities showed that the adolescents have increased knowledge about how to deal with problems at puberty, and the best score of 90. Similar coaching activities can be used as preventive measures carried out on an ongoing basis and can be developed towards regular health screenings specifically STDs for teenagers. ABSTRAK Kekurangan Energi Kronik (KEK) merupakan kondisi yang disebabkan karena adanya ketidakseimbangan asupan gizi antara energi dan protein, sehingga zat gizi yang dibutuhkan tubuh tidak tercukupi. Ibu hamil yang menderita KEK mempunyai resiko kematian ibu mendadak pada masa perinatal atau resiko melahirkan bayi dengan berat badan lahir rendah (BBLR). Gizi pada kehamilan sangat penting karena merupakan masa puncak perhatian mengenai pentingnya gizi dalam menurunkan jumlah angka bayi prematur, mortalitas bayi, dan kematian ibu. Berdasarkan wawancara pada beberapa ibu hamil, sebagian besar ibu hamil tidak mengetahui bahan pangan yang berkualitas dan mudah dijangkau yang bisa memenuhi kebutuhan gizi pada saat kehamilan. Adapun pengabdian kepada masyarakat ini akan dilakukan dengan cara Community Relation Melalui Penyuluhan Tentang.bahan- bahan pangan yang berkualitas dan mudah terjangkau dengan tujuan kegiatan ini nantinya ibu hamil KEK dapat secara mandiri untuk memenuhi kebutuhan gizinya disamping pemenuhan gzi yang diberikan oleh Puskesmas Simpang Tiga. Hasil kegiatan menggambarkan pengetahuan dan keinginan ibu hamil untuk memenuhi kebutuhan gizinya secra mandiri sangat baik dan berkesan.